Penerapan Metode Analytical Hierarchy Process (AHP) dalam Pemilihan Subkontraktor Terbaik pada PT. Tatha Group - Rio Ferdinand Situmeang; Yoshida Sary (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Subcontractor selection is a crucial factor in determining the success of a construction project. The selected subcontractor not only plays a role in expediting the completion of the work but also influences the overall quality, cost, and timeliness of the project. Mistakes in decision-making, such as selecting a less competent subcontractor, can result in delays in completion, increased project costs, and even decreased construction quality. Therefore, a systematic, measurable, and objective method is needed to support the subcontractor selection process. This study aims to implement the Analytical Hierarchy Process (AHP) method as an approach in a decision support system for subcontractor selection. AHP was chosen because it can decompose complex problems into simpler structures by determining criteria weights and comparing alternatives. The criteria used in this study include expertise, work experience, timeliness of work, equipment availability, and bid price. By assigning weights to each criterion, the selection process can be carried out more transparently and measurably. The case study was conducted at PT. Tatha Group, a company engaged in the construction services sector. In this study, AHP was used to prioritize alternative subcontractors to be selected to assist in project implementation. The research results show that the AHP method produces clear, structured results and supports more accurate decision-making. Thus, the application of AHP not only minimizes subjectivity in assessments but also provides accountable recommendations for selecting the best subcontractor for the project's needs.